PENANAMAN KARAKTER PEDULI LINGKUNGAN MELALUI PROGRAM SEKOLAH ADIWIYATA - Fatma Yudianti, Oktavia (Pendidikan Dasar - Pascasarjana Universitas Negeri Jakarta, 2020)
This research is motivated by the lack of public awareness of the environment. Many people found throwing garbage in the river, using plastic, illegal logging, and others. Given these conditions, the educational task of forming the character of caring for the environment from an early age. The objectives of the study are (1) To describe the environmental care character of the adiwiyata program for grade IV-A students at Tenggilis Mejoyo I Elementary School, Surabaya. (2) Identifying factors that support and hinder the formation of environmental care characters. This research uses a descriptive qualitative approach. The data sought in this study are class IV-A students and factors that support and inhibit. Data collection techniques through participatory observation, semi-structured interviews, and documentation. Subjects studied were class IV-A as many as 29 students. Data analysis uses data reduction, data presentation, and drawing conclusions. The results of the study there are 2 students who have the character in the criteria already entrenched, 3 students including the criteria began to develop. The character of caring for the environment through the adiwiyata school program for grade IV-A students by 89% of the category is already entrenched. Supporting factors are bringing food containers, tumblr bottles, clean Friday, hydroponics, 3R, and others. Inhibiting factors are lack of awareness of some students and lack of habituation at home.